Analysis of Premium Reserves Value in Endowment Life Insurance Using Fackler Method - Raiyan, Muhammad; Nathanael, Stevanus Albert (Indonesian Operations Research Association (IORA), 2024)
Every insurance company undoubtedly seeks to gain profit, and one of the avenues for profit comes from premium reserves, which represent the amount of money held by the insurance company during the coverage period. Various methods, including the Frackler method employed in this study, are utilized to calculate premium reserves. In the calculation process, the author requires the premium value and the sum insured paid, inputting them into the Frackler method formula. The research findings indicate that the age of an insured individual at the time of enrolling in endowment life insurance influences the premium value. Consequently, it can be concluded that as the age of the insured increases, the premium reserve required for the policy tends to be higher.